FORMATION OF ECONOMIC SUSTAINABILITY OF ENTERPRISES IN MODERN ECONOMIC CONDITIONS - Волошина, Оксана (SWorldJournal, 2020)
The article studies economic sustainability, that is the main criterion for the overall stability of the enterprise, since it’s the result of the relationship and interaction of most factors of the system of economic relations of the enterprise and is pro